Growing Brine Shrimp (Artemia) in Desalination Brine Water - Madkour, Khaled (AUC Knowledge Fountain, 2023)
Water scarcity is one of the main issues in the recent and coming decades that resulted from the growing population, increasing agricultural lands, and other current challenges. This problem led to finding alternatives to provide fresh water for domestic usage. Desalination is one of these solutions, especially in the MENA region, which has more than half of the desalination plants in the world. The desalination process has two main outputs: freshwater and highly concentrated saline water (brine water). The brine water discharge can be done in various approaches, including deep-well injection, surface water disposal, land application, effluent disposal, and evaporation ponds. The evaporation ponds are one of the most sustainable ways to discard the brine water without causing harmful impacts to the environment. However, evaporation ponds need more costs for installation and maintenance to ensure that the brine water will not deplete the groundwater. Also, the brine water in the evaporation ponds takes time to be evaporated; some studies integrate various solutions that generate a profit during the drying-up process that can compensate for the time and costs of the evaporation progress in open ponds. Artemia is a tiny crustacean that lives in hypersaline lakes and solar saltworks. Artemia represents a high- quality feed for the larval rearing of aquaculture animals utilizing non-hatched decapsulated cysts, fresh nauplii, or nauplii enriched with HUFA (Highly Unsaturated Fatty Acids) and vitamins. Artemia usage has increased with the aquaculture expansion since the 1970s. Therefore, many Artemia cysts (eggs) harvesting exploitations have been set up worldwide to fulfill the Artemia requirements. However, the aquaculture industry suffers from insufficient Artemia cyst production. Our research suggests growing Artemia (brine shrimp) in evaporation ponds of desalination brine water to feed the marine fish larvae in aquaculture by exploring Artemia growth in brine water in the short and long term and its impact on the reproductive characteristics of Artemia. Thus, it can produce income for these ponds, invest time during evaporation, reduce environmental impacts, and enhance the aquaculture industry.